Desmin disorganisation: A key feature in feline hypertrophic cardiomyopathy - Wan-Ching Cheng; Charlotte Lawson; Lois Wilkie; Melanie Dobromylsky; Virginia Luis Fuentes; Mark R. Holt; Elisabeth Ehler; David J. Connolly (PLoS ONE, 2025)
Hypertrophic cardiomyopathy is usually characterised histologically by increased ventricular wall thickness and myocyte disarray. In human and rodent HCM, subcellular alterations were detected that involve the intermediate filament cytoskeleton (mainly desmin) and proteins that are important for mechanical and electrochemical connection of the cardiomyocytes (beta-catenin and connexin-43, respectively). We demonstrate here that similar changes can be visualised in HCM samples from cats, with prominent desmin and αB-crystallin aggregates that are accompanied by increased expression at the protein level. In addition, there is a disorganisation of beta-catenin and connexin-43, which display additional aberrant signals at the lateral surface of cardiomyocytes. This suggests that the subcellular response in cardiomyocytes to HCM is shared by humans and cats.